Innovative method "DV-PIMS" technique and dental implant design for grafting injectable platelet-rich fibrin around the dental implant - Goat jaw cadaver study - Deepak M Vikhe; Seemit V Shah; Juan Blanco Carrion; Umesh G Palekar (Wolters Kluwer Medknow Publications, 2019)
Aims: Dental implants have revolutionized the treatment modality for replacing missing teeth. The ability of implants to osseointegrate with the bone leads to its success. The problem is sometimes there is inadequate bone available for implant. If hygiene is not maintained, biofilms of bacteria can be formed around the dental implant. One approach to this problem has been development of bioactive surgical additives. Platelet-rich fibrin (PRF) appears as an alternative. There are various techniques of using PRF. These techniques need skill and practice to use PRF. Objective: To evaluate implant stability and flow of injectable PRF (i-PRF) of regular implant and modified innovative design implant. Materials and Methods: Thirty goat jaw bones were selected. Implants were placed in mandibular posterior region. Fifteen implants were placed using regular dental implant system (Group A) on the left side of jaw bone. The other 15 implants were placed using modified dental implant (Group B) on the right side of jaw bone. The body of these implants at middle has drainage vents to drain/flow the i-PRF-like dye. The dye was injected through regular and modified implants (DV-PIMS technique). Then the stability was checked with the help of Periotest. Cross section was taken 3 cm away from dental implant at the angle of mandible, to check the flow of i-PRF/platelet-rich plasma (PRP)-like dye. Results: Periotest evaluation showed a mean of 2.3 for implant Group B and a mean of 1.5 for implant Group A. The flow of i-PRF-like dye was seen in Group B, and Group A does not show any flow. Conclusion: There are various techniques of using PRF. These techniques need skill and practice to use PRF. This (DV-PIMS) method aims to explain new implant design that disperses an i-PRF solution from inside out. The screw section of the new implant is made of a reservoir running vertically down inside. That reservoir is filled with (injectable) PRF, and then a cover screw is placed. The solution will begin to slowly diffuse out, through the vents in implant, keeping biofilms from forming or avoiding at the screw-bone interface and accelerate healing process.